PENGARUH FUNDAMENTAL KEUANGAN TERHADAP PEGERAKAN RETURN SAHAM (STUDI KASUS PERUSAHAAN DI KOMPAS 100) - admin, JAHARA B11112067 (Jurnal Manajemen Update, 2016)
This study examine the effect of financial fundamental on stock return movement ( case study: companies listed on Kompas 100) over period 2010-2014. This study do because many different in study with one another and there is a difference between the real condition with the theory. The sampling technique used in this study is purposive sampling. The research sample consisted of 32 companies by the observation numbers of 160 observational data. The data analysis tehnique used in this research is multiple linear regression. Hypothesis testing using f-statistics and t-statistics. The other hand, classical assumption also performed including normality test, multicolinearity test, autocorrelation test, and heteroscedasticity test. The result in this study showed Return On Assets (ROA) has positive influence and not significant on stock return changing. Earning Per Share (EPS) has negative influence and significant on stock return changing. Current Ratio (CR) has positive influence and significant on stock return changing. Debt Equity Ratio (DER) has positive influence and significant on stock return changing. Price Earning Ratio (PER) has negative influence and not significant on stock return changing. Price to Book Value has negative influence and not significant on stock return changing. Net Profit Margin Value has positive influence and not significant on stock return changing. The conclusion in this study that stock return are affected by Earning Per Share and Current Ratio. The other factors like Return On Assets, Debt Equity Ratio, Price Earning Ratio, Price to Book Value, and Net Profit Margin Value have not influence on stock return Keywords:Â  financial fundamentals, Stock returns, Compass 100 and Return On Assets (ROA), Earning Per Share (EPS), Current Ratio (CR), Debt Equity Ratio (DER), Price Earning Ratio (PER), PriceÂ  to Book Value, Net Profit Margin Value.